(untitled) (Medico Legal Update, 2021)
This study analyzes the concepts of bribery and gratification and the distinguishing parameters between them as regulated in several Articles of the Anti-Corruption Law. This involved the application of the normative legal research supported by court decisions to clarify these differences. The results of this study showed that bribery requires a meeting of mind between the bribe givers and bribe recipients which is not found in gratification. The reporting mechanism and the reversal burden of proof do not apply to bribery while Operation Catching Hand does not apply to gratification due to its inability to satisfy the provisions of Article 1 point 19 of the Criminal Procedure Code. Criminal sanctions are also imposed on both the giver and the recipient of a bribe while the act of a giver in gratification is not considered as a criminal offense. The study also found the wrong application of these essential differences in court decisions.